Feedlot performance of steers implanted with Stilbestrol prior to the grazing season. - Koch, B.A.; Smith, E.F.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
Experimental evidence indicates that beef steers implanted with low levels of stilbestrol before going to grass will make increased gains during the grazing season. The test reported herein was designed to measure the performance of such implanted steers on a fattening ration in dry-lot after the grazing season.
Keywords: Feedlot; Stilbestrol; Performance; Gain